2023
DOI: 10.3390/ijms24043302
|View full text |Cite
|
Sign up to set email alerts
|

The Gilded Clot: Review of Metal-Modulated Platelet Activation, Coagulation, and Fibrinolysis

Abstract: The processes of blood coagulation and fibrinolysis that in part maintain the physical integrity of the circulatory system and fluidity of its contents are complex as they are critical for life. While the roles played by cellular components and circulating proteins in coagulation and fibrinolysis are widely acknowledged, the impact of metals on these processes is at best underappreciated. In this narrative review we identify twenty-five metals that can modulate the activity of platelets, plasmatic coagulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Calcium plays a key role in the regulation of platelet haemostasis [56]. Dietary calcium exerts protective effects on blood platelets and decreases platelet aggregation, even when the diet is enriched with saturated fatty acids [57] or sodium [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium plays a key role in the regulation of platelet haemostasis [56]. Dietary calcium exerts protective effects on blood platelets and decreases platelet aggregation, even when the diet is enriched with saturated fatty acids [57] or sodium [58].…”
Section: Discussionmentioning
confidence: 99%
“…Little data are available on the effects of manganese on blood platelets; however, it appears that it may enhance platelet activation [56]. Nevertheless, its ability to either induce or hamper platelet aggregations has not been noted so far, despite the presence of the manganese-induced formation of pseudopodia [69].…”
Section: Discussionmentioning
confidence: 99%
“…When studying the effect of cesium on platelet activity, plasma coagulation and fibrinolysis in vitro and in vivo, it was found that in the case of in vitro coagulation, CsCl had no significant effect on factor IX (FIX) activation compared to various monovalent salts; therefore, cesium does not affect FIX activity, and the only noticeable effect of cesium is the inhibition of ADP-mediated platelet activation (Nielsen et al, 2023).…”
Section: Methodsmentioning
confidence: 99%